Expectations and implications of Japan’s ‘new’ ODA charter for Lusophone Africa under TICAD process - Raposo, Pedro Amakasu (2017)
This paper compares and asks how Japan’s ‘new’ ODA Charter is influencing the direction of its aid policy to Lusophone Africa - so-called Portuguese-speaking African Countries of Angola, Cape Verde, Guinea-Bissau, Mozambique and Sao Tome and Principe (PALOP) - in light of the TICAD process. The topic relates to Japan’s shift from traditional humanitarian and development ODA towards a more strategic agenda on behalf of the private sector, which in turn requires us to assess how the latest Development Cooperation Charter compared to previous ones and how it reflects each of them. This paper finds that although the ‘new’ Charter benefits both sides it openly favors resource-rich Angola and Mozambique at the expense of development in the poorest PALOP. It concludes that Japan’s public-private partnerships are playing a transformative role in PALOP in line with TICAD and the Africa Mining Vision, moving beyond the simple exploitation of natural resources towards broad-based sustainable growth.